2022
DOI: 10.11591/ijphs.v11i4.21873
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with utilization of visual inspection with acetic acid in Nepal

Abstract: <p>Visual inspection with acetic acid (VIA) is an optional cervical cancer screening method. National guideline of Nepal has emphasized using the VIA and intended to achieve at least a 50% screening rate by 2015 but the overall coverage is only 2.4% in 2019. A cross-sectional study was conducted to identify the factors associated with the utilization of VIA screening in Bagmati Province, Nepal. A convenience sample of 400 women aged 30 to 60 years was included in the study. A semi-structured questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…All 19 studies were cross-sectional studies 5 – 10 , 13 25 . Most studies were published in international journals ( n =14) 5 9 , 13 , 15 , 17 , 18 , 20 24 while only five studies were published in national journals 10 , 14 , 16 , 19 , 25 13 studies were community-based 5 , 7 , 10 , 13 15 , 17 21 , 23 , 24 , while six studies were hospital-based 6 , 8 , 9 , 16 , 22 , 25 The summary of included studies is shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…All 19 studies were cross-sectional studies 5 – 10 , 13 25 . Most studies were published in international journals ( n =14) 5 9 , 13 , 15 , 17 , 18 , 20 24 while only five studies were published in national journals 10 , 14 , 16 , 19 , 25 13 studies were community-based 5 , 7 , 10 , 13 15 , 17 21 , 23 , 24 , while six studies were hospital-based 6 , 8 , 9 , 16 , 22 , 25 The summary of included studies is shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Most studies ( n =14) were related to cervical cancer 5 , 8 – 10 , 13 , 14 , 16 , 17 , 19 , 20 , 22 25 . Only three studies were related to breast cancer screening 6 , 15 , 21 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations